Colville termination : hearings before the Subcommittee on Indian Affairs of the Committee on Interior and Insular Affairs, United States Senate, Eighty-ninth Congress, first session on S. 1413, a bill to provide for the termination of federal supervision over the property of the Confederated Tribes of Colville Indians located in the state of Washington and the individual members thereof, and for other purposes (U.S. Government Printing Office, 1965)
Considers (89) S. 1413 and related (89) H.R. 6331, to terminate Federal supervision of the Confederated Tribes of Colville Indians in Washington, to terminate all Indian-related services, and to settle associated land claims.